Network Cooperation Influence on Development of Innovation in Business with New Perspective of the Structural Funds for 2014–2020 - Krawiec, Stanisław; Bereś, Anna (Regional Barometer. Analyses & Prognoses, 2015)
During the time of the economy intensive development, technological progress, innovation dynamics the development of networking is quite visible. The common ground to strengthen cooperation between enterprises, research units and other entities being a part of the network cooperation are research and development works and the need to marked developed innovations. The cooperation between business and the science sector is also an integral factor to obtain support for cluster coordinators and support for a wide range of development process activities for cluster initiatives with grant from the new financial perspective 2014–2020.